2020
DOI: 10.1111/jcmm.15651
|View full text |Cite
|
Sign up to set email alerts
|

Apela improves cardiac and renal function in mice with acute myocardial infarction

Abstract: Apela was recently identified as a new ligand of the apelin peptide jejunum (APJ) receptor. The purpose of this study was to investigate the role of apela in post‐myocardial infarction (post‐MI) recovery from cardiorenal damage. A murine MI model was established, and apela was then infused subcutaneously for two weeks. Echocardiographs were performed before and after infarction at the indicated times. Renal function was evaluated by serum and urine biochemistry. Immunohistochemistry of heart and kidney tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In our previous study, we continuously injected exogenous recombinant ELA in mice with MI by osmotic pump. We found that ELA inhibited myocardial fibrosis and apoptosis of myocardial and kidney cells and improved the heart and kidney function of mice with MI 6 . Considering the multiple effects of ELA on the cardiovascular system, we speculate that cardiac function improvement is related to promoting angiogenesis, inhibiting myocardial fibrosis and apoptosis of myocardial cells.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In our previous study, we continuously injected exogenous recombinant ELA in mice with MI by osmotic pump. We found that ELA inhibited myocardial fibrosis and apoptosis of myocardial and kidney cells and improved the heart and kidney function of mice with MI 6 . Considering the multiple effects of ELA on the cardiovascular system, we speculate that cardiac function improvement is related to promoting angiogenesis, inhibiting myocardial fibrosis and apoptosis of myocardial cells.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, preliminary studies have shown that exogenous administration of recombinant ELA can improve the cardiac function of mice with acute myocardial infarction and of rats with pressure overload heart failure 6,18 . However, due to the short half‐life of ELA, it needs to be continuously administered by a subcutaneous osmotic pump, and thus, some researchers are trying to use ELA gene therapy to achieve the purpose of long‐term expression of ELA in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, similar to Ape13, Elabela which binds to APJ and activates the β-arrestin-2 and G αi signaling pathways exerts protective effects against various cardiovascular diseases and related complications (Coquerel et al, 2018;Kuba et al, 2019;Liu et al, 2019;Chen et al, 2020a;Liu et al, 2020;Ma et al, 2020;Xu, 2020). For instance, systemic administration of Elabela has been shown to improve cardiac function following acute myocardial infarction and derived cardiovascular events, including heart failure, myocardial ischemia/reperfusion (I/R) injury, arrhythmias, and stroke (Sato et al, 2017;Pan et al, 2020;Yu et al, 2020). Consistently, a link between hypertension and Elabela defect has been observed in pulmonary arterial hypertension (PAH) in both rats and humans (Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%